Neuro Fuzzy Controller for Positive Output KY Boost Converter to Reduce Output Voltage Ripple - Karthikumar, S.; Mahendran, N. (Elektronika ir Elektrotechnika, 2013)
KY boost converter is a recently invented in DC-DC converter topology by K. I. Hwu and Y. T. Yau. This converter operates in continuous conduction mode with low output voltage ripple in the order of few mV, fast transient response and settling time yielding larger voltage conversion ratio. In this work, Neuro Fuzzy control technique is proposed to reduce the output voltage ripple and to achieve fast settling time. The digitally simulated results are obtained using MATLAB/Simulink with reduced voltage ripple in the order of µV along with fast settling time. The proposed controller is devised with a microcontroller which is embedded with Neuro Fuzzy algorithm to regulate the output voltage of the converter and the experimental result has validated the simulation result. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.2351